The Influence of Sports Habits on Stress Levels of Medical Faculty Students in Surakarta City - Alif Fahran Fadillah; Dodik Nursanto (Newinera Publisher, 2024)
Stress is a problem in everyday life that is familiar to everyone, especially medical students. Exercise can reduce stress and improve mental health. If exercise is carried out routinely and regularly, it can reduce the activity of the sympathetic nerves and hypothalamic pituitary adrenals. This study aims to determine the effect of exercise habits on stress levels in students at the Faculty of Medicine in Surakarta City. The research used an analytical observational design with a cross sectional approach, with a sample size of 136 respondents consisting of 4 groups/generations. This research uses observation, interviews and questionnaires. Obtaining data from direct interviews with several students who were samples from this research was to identify exercise habits with the IPAQ (International Physical Activity Questionnaire) which were classified into 3, namely light, moderate, high and the level of stress experienced by students using the KPDS (Kessler questionnaire Psychological Distress Scale). The research results were tested using the Spearman rank correlation coefficient test. The results of the research show that there is an influence of exercise habits on the stress levels of Medical Faculty students, with a value of sig. (1-tailed) is 0.009, this value is smaller than the critical limit α = 0.01 (0.009 < 0.01), meaning there is a significant relationship or influence between exercise habits and stress levels.